Progress In Mathematics 5E (GCSE) - Murray, Les (Stanley Thornes (Publishers) Ltd, 1990)
Pupil's book 5E gives thorough coverage to National Curriculum level 10. Also included are computer programs and suggestions for the use of spreadsheets.
Keywords: Juvenile literature-Mathematics-Study and teaching (Secondary)